The memory of Ignatius of Antioch: the Martyr as a locus of Christian identity, remembering and remembered - MacDiarmid, Frazer (Wissenschaftliche Untersuchungen zum Neuen Testament, 2022)
Cover -- Title -- Acknowledgements -- Table of Contents -- Abbreviations and References -- Introduction -- Part I. The Remembering Ignatius -- Chapter 1: Patriarchs, Prophets, and Israel: Remembered and Reconstructed -- 1. Ignatius' Memory of the Heroes of Israel -- 2. Jews and Judaisers Refuted by the Memory of Israel -- 3. Docetism Refuted by the Memory of Israel -- 4. Memory of the Scriptures Transformed by Christ into a Source of Union -- 5. Conclusion -- Chapter 2: Ignatius' Inheritance of 'Extra-Christian' Memory -- 1. Antioch -- 2. Ignatius and the Pagan Cult -- 2. Ignatius and the Pagan Cult -- 2.1 Mysteries and Processions -- 2.2 The Pagan Cult and Memory -- 2.3 The Pagan Cult Baptised -- 3. Ignatius and Empire -- 3.1 Ignatius and Homonoia -- 3.2 The Thesis of Allen Brent -- 4. The Possible Contribution of Sociology -- 5. Limits and Taking it Too Far -- Part II. 'Memory Poiesis' - Ignatius as a Forger of his own Memorialisation -- Chapter 3: θνσίṽ θεοṽ: Ignatius' Self-Construction as Sacrifice -- 1. Sacrifice in Early Christianity -- 2. Ignatius' Self-References as Sacrifice -- 2.1 Romans 4.1-2 -- 2.2 Romans 2.2 -- 3. Language of Vicariousness -- 3.1 περίψημα -- 3.2 άγυίζοαι -- 3.3 άυιίψνχου -- 3.4 Language of Vicariousness - Conclusion -- 4. Étienne Decrept - a Further Theory about Ignatius' Self-Portrayal as Sacrifice -- 5. Conclusion -- Chapter 4: The Girardian Ignatius -- 1. Introduction: Girard and Patristic Theology -- 2. The Girardian System -- 2.1 Mimesis, Scapegoat, and Sacrifice -- 2.2 The Ambiguity of Mimesis -- 3. Synthesis: The Girardian Ignatius -- 3.1 Ignatius as Scapegoat for Roman Society? -- 3.2 The State of Ignatius' Communities According to Current Scholarship -- 3.3 Girardian Analysis of Ignatius' Communities -- 4. Ignatius' Self-Conception as Scapegoat -- 5. Ignatius and Mimesis -- 5.1 Nachfolge and Nachahmung.